The influence of carbon material properties on the efficiency of catalytic wet peroxide oxidation processes - Gomes, Helder (2015)
Carbon materiais are well known catalysts for activatin§ H^O^ into hydroxyl radicais (HO'), which are efficient oxidizin § agents. By making use of highly reactive HO" radicais, the elimination of organic compounds can be accomplished by catalytic wet peroxide oxidation (CWPO), a water treatment technology operating under mild conditions of pressure and temperature that hás gained importance due to the decreasing cost of H;0; and its increasing use in wastewater treatments